TRADITIONAL MARKET STRATEGIES IN THE COUNTRYSIDE IN MODERN MARKET COMPETITION (CASE STUDY OF ROKAN HULU REGENCY) - Darus Darus; Ilma Santriana Dewi; Muhammad Haris Fadhillah (Indonesian Journal of Agricultural Economics, 2021)
This study aims to determine the strategy of developing traditional markets in modern market competition in Rokan Hulu Regency based on internal factors which are strengths and weaknesses and external factors which are opportunities and threats. The research was carried out using the observation method where research data were analyzed using the IFE Matrix, EFE Matrix, IE Matrix, and SWOT Matrix. The results of the research that the IFE matrix value is 2.97 means that traditional markets have a strong internal position and are able to take advantage of their strengths in overcoming existing weaknesses. The EFE matrix value of 3.08 means that traditional markets have a relatively strong ability to take advantage of opportunities to overcome threats. The position of the Rokan Hulu Traditional Market based on the IE matrix is in Quadrant II, which means that the strategy needed by traditional markets in facing modern market competition in Rokan Hulu Regency is currently a growth and development strategy. The development of traditional market strategies in modern market competition in Rokan Hulu Regency obtained based on the SWOT matrix is to improve market functions in the community through socialization and partnership programs, improve traditional market management, improve infrastructure facilities, positive image and capability of each element directly involved in operational market through socialization and counseling.